2017
DOI: 10.3389/fmars.2017.00334
|View full text |Cite
|
Sign up to set email alerts
|

High Latitude Epipelagic and Mesopelagic Scattering Layers—A Reference for Future Arctic Ecosystem Change

Abstract: Scattering structures, including deep (>200 m) scattering layers are common in most oceans, but have not previously been properly documented in the Arctic Ocean. In this work, we combine acoustic data for distribution and abundance estimation of zooplankton and fish with biological sampling from the region west and north of Svalbard, to examine high latitude meso-and epipelagic scattering layers and their biological constituents. Our results show that typically, there was strong patchy scattering in the upper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 82 publications
(135 reference statements)
7
42
1
Order By: Relevance
“…In the eastern Norwegian Sea, the DSL also consisted of far fewer species of which the most important were krill (M. norvegica), mesopelagic fish (Maurolicus muelleri, B. glaciale), shrimps (S. arcticus, Pasiphaea multidenta, Hymenodora glaciale), and the Scyphozoan (Periphylla periphylla; Melle et al, 1993;Torgersen et al, 1997;Knutsen and Serigstad, 2001), but also included blue whiting (Micromesistius poutassou). An important difference in species composition between the earlier studies in the southeastern Norwegian Sea is the nearly complete absence of blue whiting and Mueller's pearlside (M. muelleri) found during this study in the Svalbard region and confirmed by Knutsen et al (2017).…”
Section: Diel Vertical Migration Patternscontrasting
confidence: 84%
See 4 more Smart Citations
“…In the eastern Norwegian Sea, the DSL also consisted of far fewer species of which the most important were krill (M. norvegica), mesopelagic fish (Maurolicus muelleri, B. glaciale), shrimps (S. arcticus, Pasiphaea multidenta, Hymenodora glaciale), and the Scyphozoan (Periphylla periphylla; Melle et al, 1993;Torgersen et al, 1997;Knutsen and Serigstad, 2001), but also included blue whiting (Micromesistius poutassou). An important difference in species composition between the earlier studies in the southeastern Norwegian Sea is the nearly complete absence of blue whiting and Mueller's pearlside (M. muelleri) found during this study in the Svalbard region and confirmed by Knutsen et al (2017).…”
Section: Diel Vertical Migration Patternscontrasting
confidence: 84%
“…Our results fit well with the results from these more southerly regions of the Norwegian Sea that show acoustic energy from the mesopelagic layer decreases with increasing latitude. Knutsen et al (2017) also observed this pattern of DSL backscattering intensity decreasing from the south-eastern Norwegian Sea region to Arctic waters north of Svalbard. This pattern agrees with ≪photoperiod constraint hypothesis≫ (Kaartvedt, 2008).…”
Section: Diel Vertical Migration Patternssupporting
confidence: 62%
See 3 more Smart Citations